A ideologia do processo formativo da BNCC no ensino médio do Ceará: destacando a área de Ciências Humanas e Sociais Aplicadas. - Silva, Maria Zélia Pinto da (2022)
The question of ideology of the formative process within the scope of the Common National Curricular Base (CNCB) regarding secondary education in Ceará, with emphasis on the area of applied human and social sciences, is the theme in which this research is located. Established in 2018 through Resolution CNE/CP nº 02/2017, the document presents us with a curriculum model for the last stage of basic education divided into four major areas of knowledge, in addition to formative itineraries referring to Law nº 13.415/2017. With teaching based on the development of pre-defined competences and skills, only the areas of languages and their technologies and mathematic and their technologies are mandatory in the three years of high school, and formative itineraries offered according to school feasibility, the student being able to choose the who is most interested in attending. This is what summarizes the ideological discourse presented by the CNCB, telling us that there is a commitment to integral education. In view of the above, we ask ourselves: to what extent the Ideology of the formative process of High School in Ceará, composed of areas of knowledge, and in particular the area of Applied Human and Social Sciences, with a focus on the development of skills and abilities, in addition to formative itineraries, does it really turn to the sense of integral education as proposed by the CNCB? Our hypothesis is that this sense of integral education can hardly be developed through pre-defined competences and skills for each area of knowledge, since such a teaching process focuses on the practice of know-how, leaving production in the background dialectic of knowledge. The flexibility presented can lead to a superficial formation directed to a certain area, in addition to suppressing the right to basic and free education in case the itineraries are not fully offered. With a qualitative research, using the dialecticexplanatory method to refute or prove our hypothesis, in whole or in part, an open questionnaire was applied to high school professors of the State Public Network of Ceará, in the area that turns to our problem. The main objective is to investigate to what extent the ideology of the CNCB formative process of High School in Ceará, composed of areas of knowledge, in our case the area of Applied Human and Social Sciences, focused on the development of skills and abilities, in addition to itineraries formations, it really turns to education in the integral sense. The theoretical framework of this research is based on the German philosopher Karl Marx, with his works Capital and Economic-philosophical Manuscripts of 1844 and mainly the Hungarian philosopher György Lukács, with his work The ontology of social being. For the authors, among the social complexes resulting from work, we find education both in its broad sense and in its restricted sense, which, necessarily, should have as an ideological basis human formation and the realization of human being in their work. This is, to take the thought of Lukács (1981), about a reciprocal connection between teleology and causality. Therefore, every process that goes from teleology to causality is the result of an ideology that, for Lukács, after Marx, can lead to ideology in the narrow sense, as false consciousness, but without ever prescinding from ideology in its broad sense, being through the ideology that men become aware of their reality and can act to solve, or make permanent, the possible conflicts of everyday life, which requires a formative process according to the educational model resulting from the type of work in each historical period. In addition to the philosophers mentioned, authors such as Dermeval Saviani (2013), Moacir Gadotti (1983), István Mészáros (2008) and documents that deal with education were also used. Finally, our theoretical analysis confirms our hypothesis that integral education will hardly be developed in the face of the establishment of pre-defined competences and skills for each area of knowledge, since according to the authors this type of development leads to the opposite direction of a omnilateral formative process. As for the expectations of professor surveyed, we observed in the questionnaires that they are divided in terms of the scope of an integral education, since they believe that the ideology of the formation process of High School consists of large areas of knowledge, in addition to formative itineraries, turns to integral education, while the formative process focused on the development of skills and abilities does not lead to this type of formation. Professors were still concerned about the reduction of workload and the possibility of a professor taking over the entire itinerary even without having the formation to do so. In our conclusions, we came to the understanding that the ideology of the formative process resulting from the CNCB for the final stage of basic education apparently is directed towards an integral education, however, in fact, it fulfills a social function for the continuity of the market logic based on the large-scale international evaluations, as it presents a false discourse regarding the real guidelines that are intended for true integral education.